Germanicus flamen Augustalis et la création de nouveaux flaminats à Rome - Lyasse, Emmanuel (Gerión. Revista de Historia Antigua, 2008)
Some inscriptions, which throw light on an allusion of Tacitus, teach us that Germanicus was flamen augustalis. Starting from the study of these rare elements, possible precedents and flamines created thereafter for other princes, we try to understand the meaning of this priesthood and its evolution after the death of its first holder.